Is Developing New Café & Co-Working Space In Canggu-Bali Still Feasible? (A Marketing Perspective) - Pramono, Jonathan Dharma; Lukitasari, Rimalinda; Wibawa, I Ketut (Politeknik Internasional Bali, 2024)
The café industry in Canggu is attractive for business, but also very competitive. As the village of digital nomads, combining three market segments of café, event space, and co-working space can be an attractive option for business development. Freelancers are seeking flexible workspaces along with premium-quality food and beverages. Although promising, a study to further see the feasibility is still needed. This study aims to analyze the business feasibility of establishing a café with event and workspace facilities in Canggu area. The research took an R&D approach with data collection methods of interviews, observations, and document research. This feasibility analysis took a market and marketing perspective. The Market analysis consists of market potential, competitor analysis, and market size, then the marketing analysis utilizes the 7Ps frameworks. The results show that the café, co-working, and event space concept has strong potential, demonstrating that this business model is viable for further development in the Canggu area.